EVALUASI PEMBELAJARAN BERBASIS HOTS BERBANTUAN QUIZ BASED LEARNING MATERI PENERAPAN PANCASILA UNTUK MENINGKATKAN CRITICAL THINKING SKILL SISWA KELAS V SD - Amaliya, Fadlilatul Ilmi; Alfi, Cindya; Fatih, Mohamad (STKIP Persada Khatulistiwa Sintang, 2024)
The aim of this research is to develop a Higher Order Thinking Skills (HOTS)-based learning evaluation by Quiz-Based Learning (QBL) on the subject of Pancasila application to enhance the critical thinking skills of fifth-grade students. This study employs a research and development method through the ASSURE development steps. The experimental design used was a pre-test and post-test design. The results of the study show that the media, as evaluated by media experts, received a validity score of 94%, while the score given by subject matter experts reached 90%, with both considered highly valid. Additionally, teacher responses on the feasibility aspect achieved 95%, also considered highly feasible. Lastly, the results showed an improvement on students' critical thinking skills with an N-gain score of 0.9, indicating a high level of improvement. Therefore, it can be concluded that HOTS-based learning supported by QBL on Pancasila application material is feasible to use for enhancing critical thinking skills.